Technology revolution 4.0 promotes the development of Vietnam's economic structure (Revista de Investigaciones Universidad del Quindío, 2023)
Today, when assessing the development level of each country, the development level of infrastructure is a crucial indicator. Therefore, investment in the development of production infrastructure is a priority and goes ahead of direct investment. Along with labor, capital, natural resources, etc., science and technology are considered essential resources with a significant impact on economic development. Over 35 years of innovation, our country's science and technology have made positive changes with many achievements in research and investigation, creating a scientific basis for formulating strategies and plans for economic development. Socio-economic, environmental protection, science, and technology, in association with production and life, contribute to improving productivity, quality, and efficiency of all branches and fields.
Keywords: technological revolution; technology 4.0; economic structure